Evaluation of treatment response using integrated 18F‐labeled choline positron emission tomography/magnetic resonance imaging in adolescents with intracranial non‐germinomatous germ cell tumours. Issue 9 (8th April 2015) - Tsouana, Eva; Stoneham, Sara; Fersht, Naomi; Kitchen, Neil; Gaze, Mark; Bomanji, Jamshed; Fraioli, Francesco; Hargrave, Darren; Shankar, Ananth
<x xml:space="preserve">Abstract</x> The efficacy of hybrid 18F‐Fluroethyl‐Choline (FEC) positron emission tomography (PET)/magnetic resonance imaging (MRI) was investigated as an imaging modality for diagnosis and assessment of treatment response and remission status in four patients with proven or suspected intracranial non‐germinomatous germ cell tumours (NGGCT). In two patients faint or absent choline avidity correlated with negative histology, whereas in other two patients, persistent choline avidity in the residual mass was suggestive of presence of viable tumour, subsequently confirmed histologically. We conclude that FEC‐PET/MRI may be an effective imaging tool in detecting viable residual tumour in patients with intracranial NGGCT post treatment. Pediatr Blood Cancer 2015;62:1661–1663. © 2015 Wiley Periodicals, Inc.